Timber wastes torrefaction for energy use - da Silva Grassmann, Guilherme; Rogério Andrade, Carlos; Dias Júnior, Ananias Francisco; da Silva Júnior, Francides Gomes; Otávio Brito, José (Maderas. Ciencia y Tecnología, 2016)
The experiment consists in the realization of timber wastes torrefaction at a final temperature of 280 ºC, with heating rates of 0,5 ºC.min-1, with 1 hour permanence in the final temperature. Three different types of wastes were analyzed by composition. Moisture content, bulk density, torrefied mass yield, gross calorific value, particle size, and physical and mechanical resistance were determined. Except the moisture content, the remaining variables were evaluated before and after torrefaction. The results indicated that torrefaction increased the wastes energy density . The torrefied material yield was influenced by the particle size. Bulk density was reduced; however, the mass reduction was higher than the volume reduction. The calorific value was increased for all types of torrefied wastes. Torrefied wastes friability was higher compared to in natura wastes.